BODY PROPORTIONALITY IN ACROBATIC GYMNASTS OF DIFFERENT COMPETITIVE CATEGORIES - Águeda Gutiérrez-Sánchez; Yaiza Taboada-Iglesias; Tania García-Remeseiro; Mercedes Vernetta-Santana (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
Acrobatic Gymnastics is a gymnastics discipline with a key differentiating element in terms of the role (top and base) played by the gymnasts making up the team. The establishment of the morphological profile is a determining factor as a predictor of sport performance. This study was aimed at establishing the proportional profile based on the proportionality indices of different competitive categories, and determining whether there were differences between them. The study involved 150 Spanish acrobatic gymnasts of both genders, competing nationally and internationally. The measurements were taken following the standards established by the International Society for the Advancement of Kinanthropometry. The different proportionality indices of tops and bases were analyzed, performing the comparative analysis according to the competitive categories of gymnasts. The results showed that among the female tops, there are no significant differences (p <0.05) in the analyzed variables, observing similarities in their proportionality. In all of the categories, both tops and bases have short upper and lower extremities in relation to the classification of these indices. The medium trunk length predominates in all categories except for the men's pair. Most gymnasts have a trunk of an intermediate shape, except in certain cases, when it has a trapezoid shape (tops in women's pairs and bases in men's and mixed pairs). A difference between arm span and height is observed in both tops and bases, according to their competitive category. The results suggest paying attention to these slight differences in body proportionality, in order to guide gymnasts toward a specific competitive category.